The pathway to accepting derogatory ingroup norms: The roles of compartmentalization and legitimacy. (September 2017) - Amiot, Catherine E.; Doucerain, Marina; Louis, Winnifred R.
Abstract: Objectives: The current experiment was conducted among ice hockey fans, and brings together theories of intergroup relations and self and identity literature. It investigated if perceiving strong norms in favor of derogating against fans of outgroup teams, and engaging in these behaviors oneself, leads to an increased compartmentalization of these behaviors (i.e., such that they are restricted to a particular compartment within the self). This association was expected to be especially strong when derogatory behaviors are portrayed as illegitimate. We also explored whether this compartmentalization then flows on to vitality as a well-being indicator. Method and design: Ice hockey fans supporting a diversity of NHL teams were recruited ( N = 116). The legitimacy of the derogatory behaviors was manipulated by making salient either: that these behaviors have harmful consequences for outgroup members (illegitimate condition) vs. that such behaviors can benefit the ingroup (legitimate condition). Results: The expected mediated model was supported among the entire sample. The association between engaging in the derogatory behaviors and their compartmentalization in the self was also moderated by the experimental manipulation: While participants in the illegitimate condition reported a positive link between engaging in these behaviors and their compartmentalization, participants in the legitimate condition did not show a significant association between these variables, suggesting no need for them to restrict these behaviors within themselves. Conclusions: Results are discussed in light of normative approaches, intergroup theories, and the self. Highlights: This article bring together theories of intergroup relations and notions from the self and identity literatures. We tested a mediational model whereby perceptions of ingroup norms in favor of derogatory behaviors against outgroup teams should positively predict fans' derogatory own behaviors, which in turn should predict an increased tendency to compartmentalize these behaviors in the self-concept. An experiment was conducted among ice hockey fans which manipulated the legitimacy of the derogatory behaviors (legitimate vs. illegitimate condition). We obtained support for the hypothesized mediational sequence, and for an attenuation of the need to compartmentalize the derogatory behaviors when these behaviors are portrayed as legitimate (vs. illegitimate).